HYDROGEN GAS PRODUCTIVITY FROM PEAT WATER ELECTROLYSIS WITH DISTILLED WATER INJECTED INTO AN INTERNAL COMBUSTION ENGINE (ICE) - Julianto, Eko; Binyamin, Binyamin; Gunarto, Gunarto; Rahmadi, Apri; Iwan, Muhammad (Universitas Muhammadiyah Surakarta, 2025)
Hydrogen gas is one of the alternative fuels that is currently being widely researched. HHO generator is a tool with the working principle of water electrolysis and is used to produce hydrogen gas. In some studies, peat water has been considered to be used as an electrolyte. This research uses experimental methods to obtain hydrogen gas results from peat water electrolysis. The electrolysis reactor used can handle as much as 400 ml of peat water. The electrodes are stainless steel (SS) with a large cross-sectional area of 0.01884 m2. The electric power used was 12 Volts DC and the time in the electrolysis process was 1 minute. Based on the results of the research that has been done, among others, where the increase in HC in the exhaust gas in Aquades water looks very efficient at the initial rotation at 2000 rpm which produces a thermal efficiency of 60% While in peat water the increase in HC in the exhaust gas in Aquades water looks very efficient at the initial rotation at 2000 rpm which produces a thermal efficiency of 90%. The influence of rpm and the unstable rotation of rpm causes the CO value in the exhaust gas of the vehicle to be unstable where at low rotation readings 223. 24 ppm, middle 634.94 ppm and top 606.89 ppm, it can be seen that in the upper round the value even decreases from the middle round, while in HHO peat water when the low round reading is 104.4 ppm, middle 101.94 ppm and top 121.29 ppm, it can be seen that in the upper round the value increases from the initial round to the top.